Job Satisfactionand Professional Burnout of Preschool Teachers - Polishchuk, O.; Koltunovych, T.; Andrieieva, Y.; Heisonyuk, N.; Oliinyk, M. (Lumen Scientific Publishing House, 2022)
This paper aims to determine the relationship features between preschool educators' job satisfaction and professional burnout. The research sample included 90 persons (average age 25.5, the sample is homogeneous). Following techniques were used as research instruments: “Diagnostics of communicative social competence” (N.P. Fetiskin, V.V. Kozlov, G.M. Manuilov), “Coping strategies inventory” by R. Lazarus, “Maslach Burnout Inventory Education Survey”, “Workaholism” Inventory (E.P. Ilyin), "The Multidimensional Perfectionism Scale” (P.L. Hewitt, G.L. Flett), “Job Satisfaction Survey”, “Evaluation of Personality's Satisfaction with Work”. Descriptive, Spearman's Rank correlation analysis, One-way analysis of variance were applied.Job satisfaction and its components have a large number of correlations with professional burnout. There are main negative correlations between professional burnout and job satisfaction, interest in work, relationship satisfaction, achievement satisfaction, professional responsibility, other-oriented professionalism, and specific characteristics of communicative and social competence. The main positive correlations can be seen between burnout and independence, propensity for antisocial behavior, confrontational coping, distancing coping, seeking social support. Low values on the scales of emotional burnout, reduction of professional achievements, the inclination for antisocial behavior, and high levels of self-centered perfectionism and amiability are peculiar features of preschool teachers with job satisfaction. The empirical data analysis indicated an inverse relationship between the professional burnout of preschool teachers and their job satisfaction. Based on the data analysis, we can state that one's passion for work is an agent that can counteract professional burnout, and thus it cannot be seen just as its' opposite
Keywords: job satisfaction; workaholism; professional burnout; coping strategies; perfectionism